Legal Remedies for Breach of Contract in Digital Service Agreements - Reza Kurniawan Cahya Putra; Gunawan Djajaputra (Dinasti Research, 2024)
This study examines the legal mechanisms for addressing breaches in service contracts in an increasingly complex digital era. It aims to identify legal challenges in digital transactions and provide relevant policy recommendations to enhance legal protections for digital service users. The research uses a qualitative method with a literature review as the data collection technique. The findings indicate that legal challenges in digital transactions are highly complex, especially in addressing breaches caused by technical factors, information asymmetry, and jurisdictional differences between countries. Digital contracts involving various parties from multiple locations require an adaptive and responsive legal approach to ensure user protection. Effective legal efforts include drafting clearer regulations on rights and obligations in digital contracts, implementing online dispute resolution (ODR) methods, enhancing service provider transparency, and fostering international collaboration for harmonizing digital contract law. With these policy recommendations, it is hoped that digital service users will receive adequate legal protection, creating a safe, fair, and trustworthy digital transaction environment.